Pengaruh Stress Kerja, Lingkungan Kerja, Dan Kepuasan Kerja Terhadap Turnover Intention Pada Karyawan PT. Asrindo Citraseni Satria Duri Riau - Habibatul Hidayati; Melati Karunia Rizalti (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate Turnover intention is the intention to leave an employee company and looking for alternatives other than company or other job. The purpose of this study to examine the influence of job stress variables, work environment, and job satisfaction on turnover intention of employees PT. Asrindo Citraseni Satria Duri Riau. Data collection is through distributing questionnaires to 120 respondents using purposive samplinh techniques. Sampling which is based on criteria, the authors set the sample in the study of employees PT. Asrindo Citraseni Satria Duri Riau who have worked for more than 2 years, using multiple linear regression testing with the help of the SPSS application. The results of the study show that partially the variables work stress, work environment, and job satisfaction has a positive effect on the turnover intention variable.